The organization of Drosophila genes. - Maroni, G. (DNA Sequence, 1994)
This study was designed to examine the range of size variations in the major functional elements of Drosophila genes and to test whether those size variations occur independently of each other. In a sample of 111 genes the following median values occur: leaders, 123 base pairs (bp); coding regions, 1242 bp; 3' untranslated regions (3'UTR), 246 bp; mRNAs, 1803 bp; 3' terminal exons 843 bp; and exons upstream of the last one 233 bp. Introns show a bimodal distribution with medians of 62 and 595 bp. Unexpected size correlations are evident for several of these elements. The size of the leader, for example, is correlated with the sizes of the coding region and the 3'UTR with very high levels of significance, and the size of the first intron is similarly correlated with the sizes of each of the individual components of the mature mRNA.